(untitled) (International Journal of Physiotherapy, 2015)
Background: A sedentary life style is a type of life style with no or irregular physical activity. It is a leading cause for reduced cardio - respiratory fitness and physical activity. The most of the employees working as computer personnel’s for more than five hours in a day is leading to altered physical activity and fitness. To study the effect of aerobic exercise programme on the cardio - respiratory fitness in computer using sedentary individuals. Methods: As per the inclusion criteria the thirty subjects were selected for the study, all the selected subjects were given aerobic protocol for 12 weeks. Pre and post therapeutic outcome measures were assessed for Body Mass Index was calculated using weight (kg)/ height (m2). Waist- hip ratio was measured using inch tape in centimeters, pre and post therapeutic values of Body Mass Index, Waist Hip Ratio, VO2 peak were assessed. Results: According to the data analysis, a significant difference was found between the pre and post test values of Body Mass Index, Waist- hip ratio and Vo2peak in both experimental and control groups (p<0.05), but comparatively more significant changes were found in the experimental rather than the control group(p<0.05). Conclusion: Aerobic exercise had significant influence in computer using sedentary individuals. There was a significant change in physical factors like body mass index, waist-hip ratio, and functional factors like vo2peak. Hence, it is concluded that 12weeks of aerobic exercises is effective in improving cardio vascular factors computer using sedentary individuals.